To Advocate or Not to Advocate: Determinants and Financial Consequences of CEO Activism. (27th December 2020) - Bedendo, Mascia; Siming, Linus
Abstract: Chief executive officers (CEOs) who engage in activism take public stands on issues that are largely unrelated to the core business of their firms. This study assesses the impact of CEO activism on shareholder value and investigates potential drivers behind the decision to advocate. We conduct an event study centred on a particular episode of CEO activism: the resignation of a group of business leaders from their roles as advisors to President Trump. We choose this setting since activism is likely to have a stronger impact when a CEO is politically connected. However, by engaging in advocacy, a CEO risks severing the very same political links that underlie the strength of the message. We find that shareholders react negatively to the decision to quit a presidential advisory council, which is consistent with a fear of weakening their firm's political influence. The decision to publicly advocate seems to be driven more by a CEO's personal political ideology than by a company's general involvement in corporate social responsibility. We also observe that managers are more likely to take a stand when they are protected by their firm's corporate governance rules. This study provides empirical evidence of the risks associated with CEO activism.